PERLINDUNGAN HUKUM TERHADAP NOTARIS ATAS PEMBUATAN AKTA OLEH PENGHADAP YANG DINYATAKAN PALSU (Analisis Putusan Mahkamah Agung Republik Indonesia Nomor 385 K/PID/2006) (Faculty of Law, University of Dr. Soetomo, 2018)
Issues that are commonly occur within notary public environment is concerning fake information given by client. Numerous clients commonly provide fake information and evidence in order to achieve their goals in making notarial deed published by notary public. This condition makes notary public alleged as party that conducting criminal act.The present research tries to analyze further about validity of notarial deed that is based on fake information or evidence provide by the client. Moreover, the present study tries to ratio decidendi of Indonesia Supreme Court No 385 K/PID/2006The method used in the present study is a normative legal research, namely legal research which is conducted by examining the library materials or secondary law while in finding and collecting the data is done by two approaches, namely the law and conceptual approaches. The present study concludes that notarial deed based on fake information or evidence provided by the client is canceled. Notary public is not obliged to examine validity of information coupled with evidence provided by the client. Furthermore, notary public is not responsible for criminal act although he/she publishes notarial deed with fake information or evidence provided by the client. Keywords: Legal Protection, Notary Public, Fake Evidence